2001
DOI: 10.1074/jbc.m011322200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gene Induction and Arrest Site Transcription in Yeast with Mutations in the Transcription Elongation Machinery

Abstract: In vitro, transcript elongation by RNA polymerase II is impeded by DNA sequences, DNA-bound proteins, and small ligands. Transcription elongation factor SII (TFIIS) assists RNA polymerase II to transcribe through these obstacles. There is however, little direct evidence that SII-responsive arrest sites function in living cells nor that SII facilitates readthrough in vivo. Saccharomyces cerevisiae strains lacking elongation factor SII and/or containing a point mutation in the second largest subunit of RNA polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…1) when cells are grown at permissive temperature (30°C). Thus, an spt6 mutation causes defects similar to what has been previously observed for other putative elongation mutants (63)(64)(65)68).…”
Section: Sptsupporting
confidence: 58%
“…1) when cells are grown at permissive temperature (30°C). Thus, an spt6 mutation causes defects similar to what has been previously observed for other putative elongation mutants (63)(64)(65)68).…”
Section: Sptsupporting
confidence: 58%
“…In particular, the rpb2-10 protein causes arrest at known mammalian pause sites and requires elongation factor TFIIS to overcome the arrest. Moreover, the rpb2-10 allele in combination with a dst1 (encoding TFIIS) deletion causes severe defects in the synthesis of most mRNA in vivo (29) and reduces the induction of a number of other genes (56). These observations suggest that in vivo rpb2-10 actually causes promiscuous arrest of RNA Pol II that requires TFIIS to suppress and overcome.…”
mentioning
confidence: 72%
“…For instance, no particular gene whose elongation is affected by these factors has been identified (29,45,56), although it has been suggested that transcription of long genes and genes with high GϩC content is defective with certain elongation defects (9, 43). Similarly, whole genome microarray analysis with dst1 and rpb9 alleles did not yield particular genes controlled at the level of elongation (23).…”
mentioning
confidence: 99%
“…In this sense, a Ca 2ϩ -dependent association of TFIIS with Cmd1/calmodulin has been reported (Stir- agreement with this idea, it has been reported that mRNA levels in general and specifically of ENA1, a gene required for salt tolerance, are severely affected in a actin and tubulin, resistance to killer toxin, and two dst1 background when combined with the rpb2-10 allele ORFs of unknown function. Among the genes uncov- (Lennon et al 1998;Wind-Rotolo and Reines 2001). ered using the SGA approach, HTZ1 and SOH1 particiFunction of the multicopy suppressors of soh1 dst1: pate in RNApol II transcription, GIM5 encodes for a…”
Section: Discussionmentioning
confidence: 99%
“…1999), speed the polymerization rate up and/or and Young 1995; Myers and Kornberg 2000; Davis et down (Bengal et al 1991;Chafin et al 1991;Hartzog al. 2002), and at some promoters can be recruited beet al 1998;Wada et al 1998), or reactivate arrested fore the loading of the core polymerase (Bhoite et al polymerases concomitantly to transcript cleavage (Wind 2001;Cosma et al 2001;Park et al 2001). RNApol II and Reines 2000).…”
Section: P Remessenger Rna Transcription In Eukaryotesmentioning
confidence: 99%